2021
DOI: 10.3390/jcm10153272
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous Tranexamic Acid Has Benefit for Reducing Blood Loss after Open-Wedge High Tibial Osteotomy: A Randomized Controlled Trial

Abstract: (1) Background: the purpose of this study was to investigate the efficacy and safety of intravenous (IV) administration of tranexamic acid (TXA) in patients undergoing medial opening wedge high tibial osteotomy (MOWHTO). (2) Methods: a total of 73 patients were randomly allocated into two groups (TXA group and control group). The primary outcome was total perioperative calculated blood loss after MOWHTO. Secondary outcomes included self-reported pain severity using a 10-point visual analog scale (VAS) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(31 citation statements)
references
References 41 publications
1
30
0
Order By: Relevance
“…The efficacy of TXA administration in reducing the amount of perioperative blood loss has been well established in various orthopedic procedures such as joint arthroplasty and spine surgery [13,14]. There have been several studies examining the efficacy and safety of TXA administration in knee osteotomies [10,15,27]. Kim et al demonstrated that the administration of TXA reduced total estimated blood loss and total amount of drainage after MOWHTO [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of TXA administration in reducing the amount of perioperative blood loss has been well established in various orthopedic procedures such as joint arthroplasty and spine surgery [13,14]. There have been several studies examining the efficacy and safety of TXA administration in knee osteotomies [10,15,27]. Kim et al demonstrated that the administration of TXA reduced total estimated blood loss and total amount of drainage after MOWHTO [9].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a number of randomized controlled studies have revealed the effectiveness of TXA in reducing perioperative blood loss in patients undergoing total joint arthroplasty [13,14], and a consensus has been reached regarding its efficacy in this patient population. By contrast, there have only been two randomized controlled trials dealing with this subject in osteotomies around the knee [10,15]. Consequently, clinical evidence validating routine TXA administrations in knee osteotomies is still not robust enough.…”
Section: Introductionmentioning
confidence: 99%
“…The e cacy of TXA administration in reducing the amount of perioperative blood loss has been well established in various orthopaedic procedures such as joint arthroplasty and spine surgery [13,14]. There have been several studies examining the e cacy and safety of TXA administration in knee osteotomies [10,15,27]. Kim et al demonstrated that the administration of TXA reduced total estimated blood loss and total amount of drainage after MOWHTO [9].…”
Section: Discussionmentioning
confidence: 99%
“…By contrast,there have only been two randomized controlled trials dealing with this subject in osteotomies around the knee [10,15]. Consequently, clinical evidence validating routine TXA administrations in knee osteotomies is still not robust enough.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive soft tissue release and exposed osteotomy surface in MOWHTO can result in substantial perioperative bleeding, mean total blood loss ranged from 635.0 to 882.7 mL. [16][17][18][19] Many studies have reported TXA administration in the perioperative period of MOWHTO to reduce surgical blood loss. 16,[18][19][20][21][22] Most of the studies adopted intravenous application 18 or combination of intravenous and topical applications, 22,23 and have shown that TXA can reduce surgical blood loss in patients undergoing MOWHTO.…”
Section: Introductionmentioning
confidence: 99%